CK5/6 and GATA3 Defined Phenotypes of Muscle-Invasive Bladder Cancer: Impact in Adjuvant Chemotherapy and Molecular Subtyping of Negative Cases - Koll, Florestan J.; Schwarz, Alina; Köllermann, Jens; Banek, Severine; Kluth, Luis; Wittler, Clarissa; Bankov, Katrin; Döring, Claudia; Becker, Nina; Chun, Felix K.H.; Wild, Peter J.; Reis, Henning (Frontiers in Medicine, 2022)
Introduction and Objective: Identifying patients that benefit from cisplatin-based adjuvant chemotherapy is a major issue in the management of muscle-invasive bladder cancer (MIBC). The purpose of this study is to correlate “luminal” and “basal” type protein expression with histological subtypes, to investigate the prognostic impact on survival after adjuvant chemotherapy and to define molecular consensus subtypes of “double negative” patients (i.e. without expression of CK5/6 or GATA3). Methods: We performed immunohistochemical (IHC) analysis of CK5/6 and GATA3 for surrogate molecular subtyping in 181 MIBC samples. mRNA expression profiles for molecular consensus classification were determined in CK5/6 and GATA3 (double) negative cases using a transcriptome panel with 19398 mRNA targets (HTG Molecular Diagnostics). Data of 110 patients undergoing radical cystectomy were available for survival analysis. Results: Expression of CK5/6 correlated with squamous histological subtype (96%) and expression of GATA3 was associated with micropapillary histology (100%). In the multivariate Cox-regression model, patients receiving adjuvant chemotherapy had a significant survival benefit (HR 0.19 95%CI 0.1-0.4, p<0.001) and double-negative cases had decreased OS (HR 4.07; 95%CI 1.5-10.9, p=0.005). Double negative cases were classified as NE-like (30%), stroma-rich (30%) and Ba/Sq (40%) consensus molecular subtypes and displaying different histological subtypes. Conclusion: IHC based classification was associated with histological subtypes of urothelial MIBC. IHC markers like CK5/6 and GATA3 that are used in pathological routine could help to identify patients with basal and luminal tumor characteristics. However, a two-sided classification system might not sufficiently reflect the heterogeneity of bladder cancer to make treatment decisions. Especially the group of IHC-double negative cases, as further analyzed by mRNA expression profiling, are a heterogeneous group with different implications for therapy.